Epi-ktibo an evaluation of the effectiveness of the Department of Health's expanded program on immunization to mothers in Barangay Payatas - patron, Pauline Anne M. (2012)
"This study evaluated the effectiveness of the Expanded Program on Immunization (EPI) in promoting immunization to Barangay Payatas mothers. Specifically, it focused on the behavior change communication aspect of the campaign as it looked into the role of communication materials in promoting the EPI to mothers. Utilizing the Pathways to a Health Competent Society Model and Prochaska's Transtheoretical Model of Behavior Change, this study made use of both quantitative and qualitative approaches as it determined whether the communication materials affected the knowledge, attitude and behavior of the Payatas mothers. The findings revealed that the respondents' primary source of information about immunization and vaccines was interpersonal communication from nurses, doctors and personnel inside health centers. Meanwhile, IEC materials such as posters, brochures and flipcharts did not greatly influence the respondents' knowledge about vaccines. Results also showed that the respondents have high knowledge on the general information about vaccinations such as the location where they can get vaccinations and that vaccines are good for their children. However, thay have low knowledge on what specific illnesses vaccines prevented. The respondents' attitudes and behavior on immunization was found out to be positive thus indicating that they most likely had their children immunized."